PENDIDIKAN KARAKTER DALAM MENINGKATKAN PEMAHAMAN GAMBAR DIRI ANAK REMAJA DI GEREJA BETHEL TABERNAKEL KRISTUS ALFA OMEGA BOJA - Rombe, Eni (P3M STT Kristus Alfa Omega, 2021)
Character education is one of the important things in shaping, building and developing children's character. Character education for children starts from the family. The family is the first and foremost institution for laying the foundation of character to children. It is from the family that children first learn about Christian values. The family is the first place where children get teachings and role models about good character. Good character education obtained in the family will bring each child to an understanding of the true self-image. If a teenager does not find a picture of himself that matches the truth, then what will form on him is a false image of himself. The mistake about self-image will lead teenagers to be inferior, hopeless, feeling useless and unconcerned or other negative feelings. If a teenager has the correct self-image in a charismatic perspective, the teenager will understand that his life is extraordinary created in the image and likeness of God (Gen. 1:26-27), as a person created specifically by God (Ps. 139: 13-16), as a creation that is guarded and guided by God because they are the seeds of God's eyes (Deut. 32: 9-10). The results of this study are, first, the level of character education in the family in GBT KAO Boja is in a very high category with a percentage value 83,956%. Second, the level of understanding of self-image of teenagers in the charismatic perspective in GBT KAO Boja is in the very high category with a percentage value of 87.238%. Third, it is found there is a relationship between character education in the family towards understanding self-image of teenagers in GBT KAO Boja.